The Value of Culture On the Relationship between Economics and Arts - Klamer, Arjo (Amsterdam University Press, 1997)
Culture manifests itself in everything human, including the ordinary business of everyday life. Culture and art have their own value, but economic values are also constrained. Art sponsorships and subsidies suggest a value that exceeds market price. So what is the real value of culture? Unlike the usual focus on formal problems, which has 'de-cultured' and 'de-moralized' the practice of economics, this book brings together economists, philosophers, historians, political scientists and artists to try to sort out the value of culture. This is a book not only for economists and social scientists, but also for anybody actively involved in the world of the arts and culture.